2007
DOI: 10.1128/jcm.01926-06
|View full text |Cite
|
Sign up to set email alerts
|

Development of Methods for Coordinate Measurement of Total Cell-Associated and Integrated Human Immunodeficiency Virus Type 1 (HIV-1) DNA Forms in Routine Clinical Samples: Levels Are Not Associated with Clinical Parameters, but Low Levels of Integrated HIV-1 DNA May Be Prognostic for Continued Successful Therapy

Abstract: We have adapted our established Alu PCR assay for proviral DNA and PCR for total cellular DNA to a real-time PCR format and applied these to human immunodeficiency virus (HIV)-positive specimens collected for routine determination of the plasma viral load (pVL). In a cohort of five patients, measurements of integrated viral load (iVL) and cell-associated viral load (cVL) in CD4؉ cells isolated by a single positive selection step were not indicative of HIV DNA levels in the circulation, and further analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
(58 reference statements)
3
19
1
1
Order By: Relevance
“…Furthermore, results obtained with the assay suggest that the level of integrated DNA is lower in patients on effective HAART than in patients not on HAART. Although this result may seem obvious, two prior reports failed to detect this difference (Carr et al, 2007; Ibanez et al, 1999). Our ability to detect this difference suggests our assay may be more precise than prior assays.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Furthermore, results obtained with the assay suggest that the level of integrated DNA is lower in patients on effective HAART than in patients not on HAART. Although this result may seem obvious, two prior reports failed to detect this difference (Carr et al, 2007; Ibanez et al, 1999). Our ability to detect this difference suggests our assay may be more precise than prior assays.…”
Section: Discussionmentioning
confidence: 72%
“…Second, the level of integration in HIV-infected individuals is low and detection is a further challenge since only a fraction of integration events are detectable because of the widely distributed integration sites (Agosto et al, 2007). While many studies have reported the level of total viral DNA in cells from HIV-infected individuals (Brenchley et al, 2004; Burgard et al, 2000; Debiaggi et al, 2000; Douek et al, 2002; Gibellini et al, 2004; Jubault et al, 1998; Kabamba-Mukadi et al, 2005; Kostrikis et al, 2002; Lillo et al, 2004; Ngo-Giang-Huong et al, 2001; Rouzioux et al, 2005; Viard et al, 2004; Vitone et al, 2005), only a few have reported the level of integrated DNA (Carr et al, 2007; Chun et al, 1997a; Chun et al, 1995; Chun et al, 1997b; Ibanez et al, 1999; Izopet et al, 2002; Koelsch et al, 2008; Ostrowski et al, 1999). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that there is not a standardized and accurate quantitative method for intracellular HIV-1 DNA quantification, the comparison of the results obtained from the different studies [21][22][23][24][25][26][27][28][29][30][31][32][33][38][39][40][41][42][43][44][45][46][47][48] is without doubt a difficult task.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, this inefficiency of integration results in an accumulation of unintegrated HIV-1 DNA (uDNA) in blood CD4 ϩ T cells and monocytes (7,8,11,12), as well as in lymphoid tissue (8-10), brain (13,14), and untreated patients with high or low viral loads (15,16). During untreated chronic infection, the majority of infected cells have been reported to contain only unintegrated HIV-1 DNA (7).…”
mentioning
confidence: 99%